The Effect of COVID-19 Pandemic on Psychological Wellness among Dental Students of a Malaysian Public University - Ahmad Dzulfikar Samsuddin; Azlan Jaafar; Nurul Izza Idaham; Mohamed Hisham Mohamed Jali @ Yunos (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]